The Implementation of MSME Marketing Strategies in Indonesia and Malaysia: An Effort to Develop Teaching Materials for Students - Wikan Isthika; Ratih Pramitasari; Handy Nur Cahya; Dayangku Azriani Awang Ismail; Fadia Zulfa Kanaya (International Journal Of Community Service, 2025)
Global Marketing Strategy Management for Micro, Small, and Medium Enterprises (MSMEs) in Developing Countries, Specifically Malaysia and Indonesia, plays a crucial role in supporting the economic growth of both nations. Malaysia, with its diverse ethnic composition—including Malays, Chinese, and Indians—and the establishment of the National Entrepreneur and SME Development Council (NESDC) in 2004, has successfully fostered MSME growth, achieving an average annual growth rate of 4.9%. On the other hand, Indonesia, which has the largest number of MSMEs in the world, contributing up to 60% of its GDP, also shows immense potential in this sector. However, there is a notable gap in practical understanding of marketing strategies and pricing decisions within MSMEs, particularly in academic settings in Malaysia, as observed at Lincoln University College (LUC). This research aims to provide a deeper insight into the implementation of MSME marketing strategies in Indonesia and Malaysia, and to develop a textbook that can serve as a guide for students in determining pricing and marketing strategies for new ventures. The activities include delivering material on marketing strategies in both countries and preparing a textbook that explores the aspects of marketing and pricing in depth. Expected outcomes include the publication of scholarly articles, educational videos, and a textbook that can serve as a reference for MSME development. Through this initiative, it is expected that students at LUC will enhance their knowledge of MSMEs in both countries and gain an understanding of the differences and similarities in marketing strategies implemented in Indonesia and Malaysia.